Morphology and cellular-traction of fibroblasts on 2D silk-fibroin hydrogel substrates. Issue 1 (2nd January 2022) - Edwin, Privita Edwina Rayappan George; Rajagopalan, Neeraj Raghuraman; Bajpai, Saumendra K.
ABSTRACT: Development of clinically amenable bio-implants with silk-fibroin (SF) necessitates characterization of cellular-traction generated between cells and the substrate. However, studies on the biomechanical response of cells on SF substrates are limited. In this study, we prepared SF hydrogels of varying compliance (SF30 and SF50) and varying surface-ligands (derivatized with poly-L-lysine (PLL) or Arg-Gly-Asp (RGD) peptide). Subsequently, NIH-3T3 fibroblast cells were grown on these substrates, and the morphological changes was examined. It was observed that the increase in SF stiffness from 0.7 kPa to 3.1 kPa decreased nucleus-to-cytoplasm area-ratio and increased asymmetricity along the major-axis of cells. Moreover, while functionalization of SF with RGD induced increase in cell-area and circularity, functionalization with PLL did not cause any change. Next, using traction-force-microscopy (TFM), we quantified 2D cell-traction for NIH-3T3 cells cultured on SF hydrogels. Cells plated on SF50 hydrogel exhibited significantly high traction stress as compared to SF30; change of functionalization did not show significant change. Also, protrusion traction stress was found to be greater than nuclear traction stress. Put together, our results suggest that surface-stiffness of SF-hydrogel, rather than nature of surface-ligand, regulates both cellular morphology and cellular traction stresses.